Evaluating Legal Information Literacy of Students at Rajiv Gandhi National University of Law Punjab: A Study - Kumar, Rajnish; Brar, Khushpreet Singh (DESIDOC Journal of Library & Information Technology, 2025)
This study evaluates the perceived level of Legal Information Literacy (LIL) among students at Rajiv Gandhi National Law University, Punjab (RGNLU), focusing on their proficiency across five dimensions: legal information seeking and retrieval, information evaluation, information use and application, information analysis, and information management and organisation. Employing a quantitative research design and survey method, a structured questionnaire based on BIALL standards was used. Data analysis of 178 participants shows that 68 % exhibit moderate LIL, 16.3 % demonstrate high proficiency, and 15.7 % have low LIL scores. Differences in proficiency across programs and gender highlight the need for specialised interventions and instructional approaches. The study advocates for targeted strategies, including the integration of technology and practical applications, to enhance LIL skills. Emphasising the positive impact of prolonged academic engagement, the findings offer insights for curriculum development and institutional support mechanisms, contributing to the discourse on legal education and information literacy.